Agreement of antenatal care indicators from self-reported questionnaire and the antenatal care card of women in the 2015 Pelotas birth cohort, Rio Grande do Sul, Brazil - Lina Sofia Morón-Duarte; Andrea Ramirez Varela; Diego G. Bassani; Andrea Dâmaso Bertoldi; Marlos R. Domingues; Fernando C. Wehrmeister; Mariangela Freitas Silveira (BMC, 2019)
Abstract Background Studies of healthcare service use during the pregnancy-postpartum cycle often rely on self-reported data. The reliability of self-reported information is often questioned as administrative data or medical records, such as antenatal care cards, are usually preferred. In this study, we measured the agreement of antenatal care indicators from self-reported information and antenatal care cards of pregnant women in the 2015 Pelotas Birth Cohort, Brazil. Methods In a sample of 3923 mothers, indicator agreement strengths were estimated from Kappa and prevalence-and-bias-adjusted Kappa (PABAK) coefficients. Maternal characteristics associated with indicator agreements were assessed with heterogeneity chi-squared tests. Results The self-reported questionnaire and the antenatal care card showed a moderate to high agreement in 10 of 21 (48%) antenatal care indicators that assessed care service use, clinical examination and diseases during pregnancy. Counseling indicators performed poorly. Self-reported information presented a higher frequency data and a higher sensitivity but slightly lower specificity when compared to the antenatal card. Factors associated with higher agreement between both data sources included lower maternal age, higher level of education, primiparous status, and being a recipient of health care in the public sector. Conclusions Self-reported questionnaire and antenatal care cards provided substantially different information on indicator performance. Reliance on only one source of data to assess antenatal care quality may be questionable for some indicators. From a public health perspective, it is recommended that antenatal care programs use multiple data sources to estimate quality and effectiveness of health promotion and disease prevention in pregnant women and their offspring.